Psychological and psychophysiological “price” associated with schoolteachers’ occupation - Kokun, Oleg M. (Social Welfare: Interdisciplinary Approach, 2011)
Any kind of work is normally associated with a certain psychological and psychophysiological “price”. It is most pronounced in occupations that are characterized by high professional pressure, permanent stresses and increased risk of professional burnout. The survey that targeted 765 Ukrainian school teachers has revealed that the “price” they pay by virtue of their occupation is three-fold: personal, subjective and psychosomatic.
Keywords: psychological and psychophysiological occupational “price”; school teachers; adaptation; general well-being; fatigue; state of health; state anxiety